Status and prospects of organic agriculture in the regions of Ukraine - Ткаченко, А. С. (Scientific Progress & Innovations, 2018)
The article presents data on the state of organic production in the regions of Ukraine. The theoretical aspects of organic production, organic movement and ecological consumption in Ukraine and Europe are researched. The analysis of the number of organic market operators, the total area of land with organic status and land in transition is conducted. Areas with the best trends in organic farming development are identified, as well as the interdependence between the conditions of organic farming and the number of organic operators. For the study data all regions of Ukraine were collected, except for the territory of ATO (Luhansk and Donetsk region) and the temporarily occupied territory of the Autonomous Republic of Crimea.The largest number of operators in the organic market is located in Kyiv, Odessa, Kherson, Zhytomyr and Lviv regions. The leaders in areas of organic agricultural land and land of transitional period are Odessa, Kherson, Dnipropetrovsk, Zhytomyr and Poltava regions. The largest amount of organic land is located in Odessa, Kherson, Dnipropetrovsk, Zhytomyr and Kirovograd regions. The smallest number of organic lands is differed in Chernivtsi, Sumy, Ivano-Frankivsk, Vinnytsia and Zaporizhzhia regions. The number of organic farmers in the region does not affect the number of organic market operators. Areas were identified where organic farming are absent at all – such as Chernivtsi and Sumy. It is established which factors may have an impact on the development of organic production. It is determined that education and popularization of healthy and ecologically clean food is important, as well as assistance in search of the market for organic products. The recommendations for improving the situation in the field of organic farming are presented and prospects for further research are outlined.